Implementasi Program Masjid Sebagai Pusat Pendidikan Keagamaan dan Sarana Pembinaan Masyarakat Desa Sengkuang Jaya - Septriana Putri; Vistika Natasya; Dhafi Hayanto; Oktarini; Ahmad Choky Alamsya Hidaya; Reske Oetalu; Cicih Nuryani; Ahmad Lio Saputra; Mitri Nadila; Khosi’in (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
Sengkuang Jaya Village is one of the villages in Indonesia that has quite good potential for religious development. One of the efforts made is to make the mosque a center for religious education and a means of developing village communities. The aim of this research is to determine the implementation of the mosque program as a center for religious education and a means of community development in Sengkuang Jaya Village. The research method used is a qualitative method with a case study approach. Data collection was carried out through observation, interviews and documentation. The research results show that the implementation of the mosque program as a center for religious education and a means of community development in Sengkuang Jaya Village has gone well. The programs implemented include routine recitations, Quran tahfiz classes, religious training, and community empowerment. The role of the mosque takmir, village government, and community participation are supporting factors for the success of this program. However, there are still several obstacles such as limited funds and infrastructure. It is hoped that this program can continue to be developed and become a model for other villages in empowering the community through mosques.